NUMERICAL MODELING OF SWASH ZONE MORPHOLOGICAL PROCESSES IN COARSE-GRAINED BEACHES WITH XBEACH OPEN-SOURCE MODEL - S. Maleki Taghiabad; M. Adjami; A. Ahmadi (مهندسی عمران شریف)
The swash zone and its processes are significant in a beach system due to their considerable effects on beach hydrodynamics, morphodynamics, and ecosystems, including beach flows, aquifers, and sediment transport. Developing efficient numerical models to evaluate hydrodynamic-morphodynamic processes is essential, particularly in the swash zone. XBeach is a numerical model for beach simulations. In this regard, research gaps in this field have been considered in assessing the performance of the XBeach model based on the SB and NH modules, comparing the results of morphological process simulations, and sensitivity analysis of the results under different coastal conditions. Based on this, this research is dedicated to modeling three different laboratory models with varying hydrodynamic-morphodynamic conditions to evaluate the XBeach model's performance in simulating coarse-grained beaches' morphological processes. After calibrating and sensitivity testing the models, the results are extracted and compared with laboratory models in the numerical modeling process. The results of this research indicate that the XBeach model has an acceptable performance in modeling hydrodynamic and morphodynamic processes in the Swash region, and simulation with the NH module performs better compared to the SB module (with a reduction in modeling error of over in various models). Additionally, the results show that phase errors during water infiltration/percolation into the aquifer in XBeach lead to the expansion of numerical modeling errors in calculating changes in the seabed profile and aquifer water level.